DISCOVERY LEARNING DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM: MENINGKATKAN KEMAMPUAN KOGNITIF DAN KEBERMAKNAAN BELAJAR SISWA - khoirut tobib, Ahmad syafak; syafei, Imam; sunarto, Sunarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study examines the implementation of the Discovery Learning model in Islamic Religious Education (PAI) to enhance students’ cognitive abilities and meaningful learning. Learning of Islamic Religious Education in schools is often still teacher-centered, resulting in limited development of higher-order thinking skills and meaningful understanding among students. Therefore, an innovative learning model is required to encourage active knowledge construction. This research aims to analyze the implementation of Discovery Learning and its contribution to students’ cognitive development and meaningful learning. The study employed a qualitative descriptive approach conducted at SMP Negeri 4 Bandar Lampung. Data were collected through observation, interviews, and documentation, and analyzed thematically with the assistance of NVivo software to identify patterns of learning implementation and student responses. The findings indicate that the Discovery Learning model was implemented through six stages: stimulation, problem statement, data collection, data processing, verification, and generalization. Each stage encouraged students’ active engagement in exploring concepts, analyzing information, and drawing conclusions. The implementation of this model contributed to the development of higher-order cognitive skills (C4–C6) and supported the formation of meaningful learning, where students were able to connect new knowledge with their prior experiences. These results suggest that Discovery Learning can serve as an effective instructional strategy for improving the quality of Islamic Religious Education learning.